Law of Proof in Early Modern Equity. - Macnair, Michael R. T. (Comparative studies in continental and Anglo-American legal history., 2013)
This volume is a systematic study of the rules of proof in English Courts of Equity between the later sixteenth and the early eighteenth century. In this period the proof practices of the Courts of Equity were controversial, as contemporary lawyers saw them as linked to the Civil Law, and some perceived a threat to the Common Law tradition. The reality of this linkage and threat has continued to be controversial among historians. In addition, this period saw the early stages of the development of the Common Law of Evidence, which in modern law is a striking divergence from Civil Law systems. T.